DAMPAK MODERASI EMOSI POSITIF PADA HUBUNGAN KEPUASAN KONSUMEN DAN WORD OF MOUTH POSITIF - Ivana K Wamafma (Jurnal Manajemen dan Bisnis, 2017)
This research tested the moderating impact of positive emotions during service delivery process at the influence of satisfaction to positive word-of-mouth communication. This research is stressed on the important of affective context in service consumer behavior. Unit of analysis is individual and research setting was in restaurant. Respondents were consumers who finished interact with service provider. Survey respondents were 150 restaurant consumers in Jayapura, Papua. Data analysis performed using Moderating Regression Analysis (MRA). Result of the research suggesting that customer satisfaction has a positive and significance influence on positive word-of-mouth. Positive emotions during service delivery process moderated the influence of customer satisfaction positive word-of-mouth communication at least partially, and not moderate the influence of customer satisfaction to repurchase intention.